The Contingency Plan for Oil Spills in Flow Lines in Camp Cuyabeno Petroproducción (Revista Científica Ciencias Naturales y Ambientales, 2011)
The contingency plan for hydrocarbon spills from pipelines in an investigation which took place in the Cuyabeno Petroproducción station, situated in the grounds of Amazonas and Union Nacional, Palma Roja parish, Canton Putumayo, in the north east of the Sucumbíos Province. This bio diverse area is protected, forming part of the National Forest Heritage, which inturn belongs to the Cuyabeno Faunistic Production Reserve. The contingency plan contains immediate emergency procedures to be carried out in case of emergencies. As expected, the hydrocarbon spill simulation program me was highly successful, as were two simulations themselves, one in the Dygoil river and the other in the Chespiro river, the willingness of the Environmental Protection Unit staff and Petroproducción employees to work together was fundamental in the project´s success..
Keywords: Hydrocarbons; simulation; environmental; biodiversity.